A Comparative Analysis of Recent Identification Approaches for Discrete-Event Systems. (23rd June 2010) - Estrada-Vargas, Ana Paula; López-Mellado, Ernesto; Lesage, Jean-Jacques
Abstract : Analogous to the identification of continuous dynamical systems, identification of discrete-event systems (DESs) consists of determining the mathematical model that describes the behaviour of a given ill-known or eventually unknown system from the observation of the evolution of its inputs and outputs. First, the paper overviews identification approaches of DES found in the literature, and then it provides a comparative analysis of three recent and innovative contributions.